Spouse confidence and physical function among adults with osteoarthritis: The mediating role of spouse responses to pain - Hemphill, Rachel C. (Health Psychol, 2016)
OBJECTIVE: This study of adults with osteoarthritis and their spouses examined spouse responses to patients’ pain as potential mediators of the associations between spouse confidence in patients’ ability to manage arthritis and improvements in patients’ physical function and activity levels over time. METHODS: Participants were 152 older adults with knee osteoarthritis and their spouses. In-person interviews were conducted with patients and spouses (separately) at three time points: baseline (T1), six months after baseline (T2), and 18 months after baseline (T3). At each time point, patients reported their self-efficacy for arthritis management, functional limitations, and time spent in physical activity; spouses reported their confidence for patients’ arthritis management and their empathic, solicitous, and punishing responses to patients’ pain. Multiple mediation regression models were used to examine hypothesized associations across two distinct time frames: six months (T1–T2) and 12 months (T2–T3). RESULTS: Across six months, spouse confidence was indirectly related to improvements in patients’ functional limitations and activity levels through increased empathic responses to patient pain. Across 12 months, spouse confidence was indirectly related to improvements in patients’ functional limitations and activity levels through decreased solicitous responses to patient pain. CONCLUSIONS: This study adds to the literature on spousal influences on health by identifying two spouse behaviors that help to explain how spouse confidence for patients’ illness management translates into improvements in patients’ physical health over time. Findings can inform the development of couple-focused illness management interventions aiming to increase the positive influence of the spouse on patients’ health behaviors and outcomes.